2020
DOI: 10.1002/solr.201900542
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of BaTaO2N Thin Films by Interfacial Reactions of BaCO3/Ta3N5 Layers on a Ta Substrate and Resulting High Photoanode Efficiencies During Water Splitting

Abstract: Thin films of barium tantalum oxynitride (BaTaO2N) with thicknesses of 150–680 nm are grown on TaN/Ta substrates via the interfacial reaction of BaCO3/Ta3N5 layers in a N2 atmosphere. A TaN thin film is first deposited on a Ta substrate by the Ar/N2 ion sputtering of a Ta target, and then covered with a TaOx layer by Ar/O2 sputtering. The TaOx layer is subsequently nitrided in an NH3 flow to a Ta3N5 layer. Finally, Ba metal is deposited on the Ta3N5/TaN/Ta substrate under vacuum, oxidized, and carbonized to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
0
17
1
Order By: Relevance
“…Such behavior is caused by a charge transfer favored with high overpotentials. Compared with the previously reported photocurrent densities of BaTaO 2 N, 15,52 the photocurrent densities of the BaTaO 2 N samples in this study are lower due to different pH values of electrolyte solutions. It is important to mention that K 3 PO 4 electrolyte (pH = 13) has been used in previous studies, while electrolyte based on Na 2 SO 4 (pH around 7) was used in this study.…”
Section: Resultscontrasting
confidence: 97%
See 1 more Smart Citation
“…Such behavior is caused by a charge transfer favored with high overpotentials. Compared with the previously reported photocurrent densities of BaTaO 2 N, 15,52 the photocurrent densities of the BaTaO 2 N samples in this study are lower due to different pH values of electrolyte solutions. It is important to mention that K 3 PO 4 electrolyte (pH = 13) has been used in previous studies, while electrolyte based on Na 2 SO 4 (pH around 7) was used in this study.…”
Section: Resultscontrasting
confidence: 97%
“…Further, a 4.6 mA•cm −2 photocurrent was yielded for BaTaO 2 N upon combination with Ta 2 N/Ta and modification with CoO x cocatalyst at 1.2 V vs RHE, while 9% incident photon-to-current efficiency (IPCE) at 600 nm was realized during simulated sunlight-driven water oxidation reaction. 15 Annealing of inactive as-synthesized BaTaO 2 N particles in Ar was found to be advantageous to maximize the photocurrent to 6.5 mA•cm −2 at 1.23 V vs RHE, which showed good stability over 24 h (79% initial photocurrent was retained). 16 Very recently, Castelli and co-workers 17 found that the theoretical overpotential of the TaO 2 N-(100) surface of BaTaO 2 N can be effectively decreased to 0.37 V under (photo)electrochemical conditions by applying 1% tensile uniaxial strain.…”
Section: Introductionmentioning
confidence: 97%
“…13 The CoO x -deposited BaTaO 4.6 mA cm −2 at 1.2 V vs RHE and exhibited a 9% IPCE at 600 nm during water oxidation under simulated sunlight. 14 Further, an unprecedented photocurrent of 6.5 mA cm −2 at 1.23 V vs RHE was achieved for Ar-annealed BaTaO 2 N during sunlightdriven water oxidation. 15 Although the photocatalytic and photoelectrochemical water-splitting efficiencies of BaTaO 2 N have been progressively improved, it is still far from the requirements set for practical applications.…”
Section: Introductionmentioning
confidence: 88%
“…This outcome is in agreement with the results obtained from previous photoelectrochemical analyses of BaTaO 2 N electrodes, in which oxygen evolution was enhanced at higher pH values. 20 Fig. 10 plots the apparent quantum yield (AQY) obtained from Rh/Cr 2 O 3 /IrO 2 -loaded BaTaO 2 N, together with the optical absorption of the material.…”
Section: Effects Of Cocatalystsmentioning
confidence: 99%